Screening, diagnosis and management of diabetic sensorimotor polyneuropathy in clinical practice: International expert consensus recommendations. (April 2022) - Ziegler, Dan; Tesfaye, Solomon; Spallone, Vincenza; Gurieva, Irina; Al Kaabi, Juma; Mankovsky, Boris; Martinka, Emil; Radulian, Gabriela; Nguyen, Khue Thy; Stirban, Alin O; Tankova, Tsvetalina; Varkonyi, Tamás; et al.
Abstract: Diabetic sensorimotor polyneuropathy (DSPN) affects around one third of people with diabetes and accounts for considerable morbidity, increased risk of mortality, reduced quality of life, and increased health care costs resulting particularly from neuropathic pain and foot ulcers. Painful DSPN is encountered in 13–26% of diabetes patients, while up to 50% of patients with DSPN may be asymptomatic. Unfortunately, DSPN still remains inadequately diagnosed and treated. Herein we provide international expert consensus recommendations and algorithms for screening, diagnosis, and treatment of DSPN in clinical practice derived from a Delphi process. Typical neuropathic symptoms include pain, paresthesias, and numbness particularly in the feet and calves. Clinical diagnosis of DSPN is based on neuropathic symptoms and signs (deficits). Management of DSPN includes three cornerstones: (1) lifestyle modification, optimal diabetes treatment aimed at near-normoglycemia, and multifactorial cardiovascular risk intervention, (2) pathogenetically oriented pharmacotherapy (e.g. α-lipoic acid and benfotiamine), and (3) symptomatic treatment of neuropathic pain including analgesic pharmacotherapy (antidepressants, anticonvulsants, opioids, capsaicin 8% patch and combinations, if required) and non-pharmacological options. Considering the individual risk profile, pain management should not only aim at pain relief, but also allow for improvement in quality of sleep, functionality, and general quality of life.